2020
DOI: 10.1002/fsn3.1746
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of beef broth processing technology and isolation and identification of flavor peptides by consecutive chromatography and LC‐QTOF‐MS/MS

Abstract: To investigate the flavor peptides of beef broth obtained under optimized stewing conditions, separation procedures such as ultrafiltration, Sephadex G‐15 column chromatography, and reversed‐phase high‐performance liquid chromatography were employed to isolate the umami taste peptides. Sensory evaluation was combined with liquid chromatography–mass spectrometry to detect the flavor peptides. The optimization of the stewing process conditions was studied using the orthogonal method, which indicated that time ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In the present study, the high antioxidant capacity of extracts is thought to be because of high quercetin and catechin content. A past study reported high antioxidant activity toward DPPH (8.3-49.7%), which was correlated with their polyphenol contents (1.7−9.86%) in the different artichoke samples [15]. Moreover, the other study about the artichoke byproducts showed a relatively high free radical scavenging activity and capacity to inhibit lipid peroxidation in artichoke byproducts [34].…”
Section: Antioxidant Activitymentioning
confidence: 76%
See 2 more Smart Citations
“…In the present study, the high antioxidant capacity of extracts is thought to be because of high quercetin and catechin content. A past study reported high antioxidant activity toward DPPH (8.3-49.7%), which was correlated with their polyphenol contents (1.7−9.86%) in the different artichoke samples [15]. Moreover, the other study about the artichoke byproducts showed a relatively high free radical scavenging activity and capacity to inhibit lipid peroxidation in artichoke byproducts [34].…”
Section: Antioxidant Activitymentioning
confidence: 76%
“…This compound improves meat quality and oxidative stress [30] and can be used as an antioxidant and antimicrobial agent in meat products [9]. Besides the antioxidant properties of luteolin (trans-4-Hydroxy-3-methoxycinnamic acid), catechin and caffeic acid, which were isolated from plants, these compounds also have anti-inflammatory and anticancer activities [15]. The other compounds identified and quantified in the present study are as follows; 7-neohesperidoside (7.05%), (−)-Epigallocatechin…”
Section: Identification and Quantification Of Polyphenols By Lc-qtof-msmentioning
confidence: 99%
See 1 more Smart Citation
“…Umami peptides have been gradually accepted as novel umami ingredients due to safe food source, potential function and unique taste. Umami peptides have been increasingly isolated from various food sources, such as soy sauce in ALPEEV, 9 bean in GENEEEDSGAIVTVK(GK‐15), 10 beef in SDEEVEH 11 . Gao et al 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Umami peptides have been increasingly isolated from various food sources, such as soy sauce in ALPEEV, 9 bean in GENEEEDSGAIVTVK(GK-15), 10 beef in SDEEVEH. 11 Gao et al 12 have isolated and purified five umami peptides from preserved egg yolk. Porcine bone might also be a potential source of umami peptides, but there are few studies on porcine bone umami peptides yet and its taste characteristics and synergistic effects are not yet clear.…”
Section: Introductionmentioning
confidence: 99%